Dr. Ginger Blalock: Finding My Educational Path—I Was Never Bored Again. (January 2023) - Higgins, Kyle; Boone, Randall
Dr. Ginger Blalock has been an elementary and secondary special educator, a community college career counselor and instructor, and a professor of special education. Her teaching areas included learning disabilities, instructional methods in special education, career development/transition education, paraprofessional preparation, trends/issues in special education for doctoral students, and strategies to support inclusive education. Her research primarily focused on preparing diverse youth with support needs for adulthood. Publications included chapters on strategies for collaboration, Transition and Students with Learning Disabilities, (lead co-author) Using Community Transition Teams to Improve Transition Services (lead co-author), and the transition module series published by PRO-ED, Inc. She retired after 21 years at the University of New Mexico as professor emerita, where she held numerous roles, including division director of educational specialties, program coordinator (chair) of special education, and coordinator of the Special Education Emphasis in Learning/Behavioral Exceptionalities.